Efektivitas Intervensi Psikologis terhadap Kenakalan Siswa di SMP Muhammadiyah 49 Medan - Nurul Badri Girsang, Hamidah (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
Student delinquency is a prevalent issue among adolescents that affects the school environment and the learning process. This study aims to measure the effectiveness of psychological interventions in reducing delinquency among students at SMP Muhammadiyah 49 Medan. The research utilizes an experimental method with a pre-test and post-test design. The population consists of students with records of problematic behavior, with a randomly selected sample. The intervention includes group counseling and emotional control training programs. The results indicate a significant reduction in students' delinquency levels following the psychological intervention. This finding suggests that psychological interventions are effective in reducing negative behaviors among students and enhancing a positive learning atmosphere. The recommendation for schools is to incorporate sustained psychological intervention programs as preventive and corrective measures against student delinquency.